2019
DOI: 10.1038/s41598-018-38235-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of doxycycline-mediated protection of aortic function and structure in a mouse model of Marfan syndrome-associated aortic aneurysm

Abstract: Aortic aneurysm is the most life-threatening complication in Marfan syndrome (MFS) patients. Doxycycline, a nonselective matrix metalloproteinases inhibitor, was reported to improve the contractile function and elastic fiber structure and organization in a Marfan mouse aorta using ex vivo small chamber myography. In this study, we assessed the hypothesis that a long-term treatment with doxycycline would reduce aortic root growth, improve aortic wall elasticity as measured by pulse wave velocity, and improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 76 publications
(80 reference statements)
2
24
0
Order By: Relevance
“…As a follow up study to our previous report, in the present study, we sought to quantitatively assess the anti-remodelling effects of long-term doxycycline treatment on the aortic ultrastructure of an established MFS mouse model using MPM 10 . This will compliment our recently reported comprehensive in vivo evaluation of aortic function and structure in live MFS mice subjected to a long-term treatment with doxycycline using ultrasound imaging 9 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As a follow up study to our previous report, in the present study, we sought to quantitatively assess the anti-remodelling effects of long-term doxycycline treatment on the aortic ultrastructure of an established MFS mouse model using MPM 10 . This will compliment our recently reported comprehensive in vivo evaluation of aortic function and structure in live MFS mice subjected to a long-term treatment with doxycycline using ultrasound imaging 9 .…”
Section: Discussionsupporting
confidence: 76%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Doxycycline, a nonspecific broad spectrum MMP inhibitor, has been shown by our group and others to be more effective than the current "gold standard" β-blocker atenolol at attenuating MFS-associated aortic widening, and improving elastic fiber integrity and vascular function in the MFS mouse through its inhibition of MMP-2 and -9 7,22,23 . More recently, we have shown that long-term doxycycline treatment could also correct PWV starting after 18 weeks of treatment, a clinically relevant determinant of changes in aortic wall stiffness and elasticity, which is closely associated with disease progression 9 . Although previous reports have characterized the anti-remodelling effects of doxycycline treatment on elastic fiber integrity in the aorta of MFS mice, these data were analysed using classical histological techniques involving tissue fixation and staining which can alter native vessel morphology 5,7,8,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In the mouse model of MFS, we have previously shown that doxycycline, an antibiotic and a general inhibitor of MMPs, could correct aortic elastin fibre structure and organization and was more effective than atenolol in preventing thoracic aortic aneurysm. 50,51 Another study in our laboratory reported that drug therapy with losartan and doxycycline completely suppressed aneurysm formation in MFS mice, improved elastic fibre organization, downregulated MMP-2/-9 and TGF-b1 expression, and normalized aortic contractile and relaxation function to control values. 52 Although the implication of the findings in this study is to treat these patients with MMP inhibitors, the unsuccessful results of clinical trials of ARBs have shown that there needs to be caution in extrapolating animal model results to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the serum concentration, a reduction in aneurysm growth of 33–66% was observed in the mouse model [ 14 ]. In a recently published experimental study on the development of aortic aneurysms in Marfan syndrome, the therapeutic efficacy of doxycycline was confirmed [ 19 ].…”
Section: Introductionmentioning
confidence: 99%